Which drugs are being treated patients with bipolar affective disorder in Colombia - Machado-Alba, Jorge Enrique; Fonseca, Alejandra; Machado-Duque, Manuel E; Calderón, Viviana (Universidad y Salud, 2023)
Introduction: Bipolar disorder (BP) is a serious psychiatric condition characterized by progressive changes in social and cognitive functions. Objective: To determine which medications are being used to treat a group of patients diagnosed with BP who receive treatment from the Colombian Health System. Materials and methods: Cross-sectional study to identify medication prescriptions of outpatients (regardless of their age) using a population database. Sociodemographic, clinical, and pharmacological variables were considered, searching for medications that are both approved and not approved by regulatory agencies. Results: 1,334 patients were identified, who had a mean age of 40.2±18.5 years, 50% of which were women. A total of 809 (60.6%) patients followed monotherapy, mainly using valproic acid (286/615 patients, 46.4%), quetiapine (259/525, 49.3%), and lithium carbonate (98/275, 35.6%). The most common combination of medications to treat these patients were valproic acid combined with quetiapine (n=162, 12.1%), valproic acid combined with risperidone (n=73, 5.5%), and lithium carbonate combined with quetiapine (n=62, 4,6%). 57.4% (n=766) of patients had prescriptions with non-approved medications. Conclusions: BP patients are mostly treated with monotherapy and more than half of them received drugs that are not approved.